PENGARUH KOMUNIKASI, ETIKA KERJA DAN KEDISIPLINAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI KANTOR CAMAT KECAMATAN SIBOLGA KOTA - Ittoki Josua Pakpahan; Rudi Herwin; Imelda Susanti; Emmy Fauziah Marpaung; Novita Rizki Harahap (Universitas Islam Islam Sumatera Utara, 2020)
This research aims to determine and analyze : 1) the effect of communication on the productivity employees of the Kantor Camat Sibolga Kota; 2) the effect of work ethics on the productivity employees of the Kantor Camat Sibolga Kota employees; 3) the influence of discipline on the productivity employee of the Kantor Camat Sibolga Kota; and 4) the effect of communication, work ethics and discipline on the productivity employees of the Kantor Camat Sibolga Kota. This type of research is associative research, with a sample of 56 people. The results showed : 1) communication had a positive and significant effect on the productivity employee of the Kantor Camat Sibolga Kota; 2) Work ethics have a positive and significant effect on the productivity employees of the Kantor Camat Sibolga Kota employees; 3) Discipline has a positive and significant effect on the productivity employees of the Kantor Camat Sibolga Kota employees; 4) Simultaneous communication, work ethics and discipline have positive and significant effect on the productivity employees of the Kantor Camat Sibolga Kota employees. Productivity employees can be influenced by communication, work ethics and discipline by 61.8%. While the remaining 38.2% is influenced by other variables not examined in this research.